Fredholm quasi-linear manifolds and degree of Fredholm quasi-linear mapping between them - Abbasov, A. (Український математичний журнал, 2011)
In this article a new class of Banach manifolds and a new class of mappings between them are presented and also the theory of degree of such mappings is given. Представлено новий клас многовидів Банаха та новий клас відображень між ними, а також наведено теорію степеня таких відображень.